Egyptian Novel Goose Parvovirus in Immune Organs of Naturally Infected Ducks: Next-Generation Sequencing, Immunohistochemical Signals, and Comparative Analysis of Pathological Changes Using Multiple Correspondence and Hierarchical Clustering Approach - Mohamed A. Lebdah; Amal A. M. Eid; Reham M. ElBakrey; Abd Elgalil. El-Gohary; Mohamed G. Seadawy; Mohamed R. Mousa; Hagar F. Gouda; Nehal I. A. Goda; Mostafa F. El-Hosseny; Ahmed S. El-tahlawy; Rokayya Sami; Rasha A. Al-Eisa; et al. (Viruses)
The present study aims to better understand the nature of currently circulating GPV strains and their pathological impact on the immune system during natural outbreaks among different duck breeds in Egypt. For this purpose, 99 ducks (25 flocks) of different breeds, aged 14–75 days, were clinically examined, and 75 tissue pools from the thymus, bursa of Fabricius, and spleen were submitted for virus detection and identification. Clinical and postmortem findings were suggestive of GPV infection. Concerning the immune system organs, atrophy in the thymus (60.6%), bursa (45.5%), and spleen (38.3%) was the most common gross lesion. Microscopically, the pathological impact of the virus was exhibited by a necrotic thymic cortex with Hassall’s corpuscle disintegration, the disappearance of normal bursal histological morphology accompanied by atrophied follicles and lymphocytic depletion, and apoptosis of B-lymphocytes in lymphoid follicles of the spleen. Furthermore, immunohistochemical examination revealed positive signals of the parvovirus detected in thymic lymphocytes in the cortex, bursa-dependent lymphoid follicle of the medulla, and diffuse positive expression of viral antigens in the spleen. GPV was detected in ducks using polymerase chain reaction, with the highest percentage of positive detection in the bursa of Fabricius (76%). Next-generation sequencing and phylogenetic analysis revealed that the detected virus was a variant of GPV, globally named novel GPV (NGPV), and closely related to Chinese NGPV isolates. To our knowledge, the current study is pioneering to address the immunopathological impact of NGPV among naturally infected ducks confirmed with full genome sequencing and immunohistochemical identification worldwide.